Anti‐interleukin‐5‐neutralizing antibody attenuates caradiac injury and cadiac dysfunction by aggravating the inflammatory response in doxorubicin‐treated mice. (12th March 2020) - Xiao, Dan; Zhan, Yingying; Yang, Zicong; Fan, Cao; Liu, Ling; Lin, Yingzhong
Abstract: Previous studies have demonstrated that interleukins (ILs) are closely associated with doxorubicin (DOX)‐induced cardiac injury. IL‐5 is an important member of the IL family, and this study was performed to investigate whether IL‐5 affects DOX‐induced cardiac injury and its underlying mechanisms. The cardiac IL‐5 expression was first detected and the results showed that cardiac IL‐5 levels were significantly lower in DOX‐treated mice, and IL‐5 was mainly derived from cardiac macrophage (Mø). In addition, some DOX‐treated mice received an injection of anti‐IL‐5‐neutralizing antibody (nAb), and we found that treatment with a mouse anti‐IL‐5 nAb significantly upregulated the levels of myocardial injury markers, aggravated cardiac dysfunction, increased M1 macrophage (Mø1) and decreased M2 macrophage (Mø2) differentiation, and promoted apoptotic marker expression. Furthermore, the effect of mouse IL‐5 nAb on DOX‐induced Mø differentiation and its role on mouse cardiomyocyte (MCM) cells apoptosis were detected in vitro, and the results exhibited that mouse IL‐5 nAb promoted Mø1 differentiation but inhibited Mø2 differentiation in vitro and alleviated apoptosis in MCM cells. Our results found a mouse anti‐IL‐5 nAb‐aggravated DOX‐induced cardiac injury and dysfunction by alleviating the inflammatory response and myocardial cell apoptosis.